A randomized controlled comparison of the Bonfils fiberscope and the GlideScope Cobalt AVL video laryngoscope for visualization of the larynx and intubation of the trachea in infants and small children with normal airways. Issue 10 (18th March 2013) - Kaufmann, Jost; Laschat, Michael; Hellmich, Martin; Wappler, Frank; Cote, Charles
Summary Background The Bonfils fiberscope (BF) used without the assistance of a laryngoscope failed to improve the view of direct laryngoscopy in children with normal airways. We hypothesized that if BF is supported by a laryngoscope—as recommended by its inventor—it can provide comparably good visualization of the glottis as the GlideScope® Cobalt AVL video laryngoscope (GS). Methods We included 100 children with normal airways in a randomized controlled trial. The study consisted of assessing the airway by direct laryngoscopy (DL), followed by intubation using either the BF or the GlideScope. Main outcome measures were the quality of visualization of the larynx by the percentage of glottis opening seen (POGO) and the time needed for intubation of the trachea. Results Visualization of the larynx (POGO) using the BF was significantly better than with DL (P = 0.016) or with GS (P = 0.001). The DL provided an allover better visualization than GS, although this difference was not significant and solely attributable to children weighing <15 kg. Intubation was successful in all cases with both devices. The time needed for intubation was shorter using the BF (36 ± 8 s) than with the GlideScope (49 ± 12 s, P < 0.001). Conclusion The Bonfils fiberscope significantly improved the view on the larynx compared with direct laryngoscopy and the GlideScope and enables shorter intubation time than with the GlideScope.